Arthroscopic surgery of the Wrist - Fitzpatrick, Deanne (Operating Room Nurses Association of Canada Journal, 1989)
Wrist arthroscopy is a recent development in the ﬁeld of orthopaedics. Clinical use of the arthroscope in North America began in the 1970's and revolutionized the management of knee problems. Patients undergoing arthroscopic knee surgery tend to rehabilitate more quickly and experience less pain post-operatively than patients undergoing invasive sur- gery. Infections following arthroscopy are rare, and in most cases, arthroscopic procedures are performed on an outpatient basis.